The whole library handbook 4 : current data, professional advice, and curiosa about libraries and library services - Eberhart, George M. (American Library Association, 2006)
Now in its fourth version, The Whole Library Handbook is a one-volume encyclopedia of library history, demographics, folklore, humor, current events, and popular wisdom. The new volume is organized in easy-to-find general categories, including types of libraries, the profession, people, materials, special users, operations, technology, promotion, issues, and librariana. Readers will find fascinating bits of trivia, as well as humorous sections on "how many academic librarians does it take to change a lightbulb?" and "advice from naughty library assistants." Also included are thoughtful essays.